Numerical flow simulation in the post-endoscopic sinus surgery nasal cavity - Xiong, Guanxia; Zhan, Jiemin; Zuo, Kejun; Li, Jianfeng; Rong, Liangwan; Xu, Geng (Medical & biological engineering & computing, 2008)
In this study we utilized computational fluid dynamic (CFD) techniques to construct a numerical simulation of nasal cavity airflow pre and post virtual functional endoscopic surgery (FESS). A healthy subject was selected, and CFD techniques were then applied to construct an anatomically and proportionally accurate three-dimensional nasal model based on nasal CT scans. A virtual FESS intervention was performed numerically on the normal nasal model using Fluent software. Navier-Stokes and continuity equations were used to calculate and compare airflow, velocity, distribution and pressure in both the pre and post FESS models. In the post-FESS model, there was an increase in airflow distribution in the maxillary, ethmoid and sphenoid sinuses, and a 13% increase through the area connecting the middle meatus and the surgically opened ethmoid. There was a gradual decrease in nasal resistance in the posterior ethmoid sinus region following FESS. These findings highlight the potential of this technique as a powerful preoperative assessment tool to aid clinical decision-making.